2018
DOI: 10.4049/jimmunol.1800311
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TGF-β and Phosphatidylinositol 3-Kinase Signals Modulate Distinct Metabolism of Regulatory T Cell Subsets

Abstract: Murine Foxp3 regulatory T cells (Tregs) differentiated in vitro (induced Tregs [iTregs]) in the presence of anti-inflammatory cytokine TGF-β rely predominantly upon lipid oxidation to fuel mitochondrial oxidative phosphorylation. Foxp3 expression underlies this metabolic preference, as it suppresses glycolysis and drives oxidative phosphorylation. In this study, we show that in contrast to iTregs, thymic-derived Tregs (tTregs), engage in glycolysis and glutaminolysis at levels comparable to effector T cells de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 27 publications
(36 reference statements)
9
53
1
Order By: Relevance
“…Interestingly, the basal oxygen consumption rate (OCR, correlating with OXPHOS) was significantly lower in Treg-than Th1-polarizing conditions (p<0.01; Figure 6A). These data are in accord with a recent study that reported a lower OXPHOS and glycolysis in activated tTreg as well as TGFβ-induced Treg as compared to Th0 and Th1 polarized cells (Priyadharshini et al, 2018). The lower OXPHOS in Treg cells (as compared to Th1) was associated with an augmented glycolysis, measured as a function of the extracellular acidification rate (ECAR, Figure 6A).…”
Section: Augmented αKg-dependent Tca Cycling and Oxphos Negatively Resupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the basal oxygen consumption rate (OCR, correlating with OXPHOS) was significantly lower in Treg-than Th1-polarizing conditions (p<0.01; Figure 6A). These data are in accord with a recent study that reported a lower OXPHOS and glycolysis in activated tTreg as well as TGFβ-induced Treg as compared to Th0 and Th1 polarized cells (Priyadharshini et al, 2018). The lower OXPHOS in Treg cells (as compared to Th1) was associated with an augmented glycolysis, measured as a function of the extracellular acidification rate (ECAR, Figure 6A).…”
Section: Augmented αKg-dependent Tca Cycling and Oxphos Negatively Resupporting
confidence: 92%
“…Tregs have been found to exhibit increased OXPHOS as compared to Teff subsets (Angelin et al, 2017;Gerriets et al, 2016;Gerriets et al, 2015;Michalek et al, 2011) but within tumors, Tregs exhibit a gene signature consistent with glycolysis (Pacella et al, 2018). Furthermore, while thymic Treg (tTreg) function was found to be dependent on mitochondrial complex III function (Koch et al, 2009), the level of OXPHOS in induced Tregs was reported to be significantly lower than in either tTreg or Th1 cells (Priyadharshini et al, 2018). In accord with the latter study, we detected significantly lower levels of OXPHOS following activation under Treg-polarizing than Th1-polarizing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with Etx did not impact differentiation of other T effector cell populations (62). This dependence on OXPHOS for iTreg differentiation is not observed for thymic Tregs which rely on glycolysis (64). Together with our data, these findings support the use of the OXPHOS pathway in T cells as a mechanism to drive differentiation of T cells along pathways that dampen the immune response, either through Treg differentiation or decreased sensitivity.…”
Section: Discussionsupporting
confidence: 79%
“…Cells with high ψ m produced four times more IFN-γ compared to low ψ m cells and cells with low ψ m showed a reduction in mTORC1 activity [103]. In another study, the addition of TGF-β reduced glycolytic metabolism in thymus Tregs, as a consequence of the reduction of mTOR pathway activation [104]. These data corroborate our findings that cells producing less IFN-γ, after treatment with MSC-EVs, have lower ψ m and may also suggest the participation of TGF-β pathway in this regulation.…”
Section: Discussionmentioning
confidence: 96%